2019
DOI: 10.5812/mejrh.92612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Swimming Training and Crocin Consumption on Intrinsic Apoptosis Pathway in Muscle Tissue of High-Fat Diet-induced Obese Rats

Abstract: Background: Obesity is a multi-factorial physical disorder that can lead to motor disorders and muscle mass loss. On the other hand, regular exercises and crocin consumption can exert anti-apoptotic effects. Objectives: The aim of this study was to investigate the effect of eight weeks of swimming training along with crocin consumption on the intrinsic apoptosis pathway in muscle tissue of obese rats. Methods: In this experimental study, 35 obese male Sprague Dawley rats (age: 16 weeks; weight: 390.12 ± 38.11)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…After a one-week adaptation to the laboratory environment, 24 rats were fed with standard HFD. To induce obesity, a fatty diet containing 45% of total energy from fat (20% soybean oil and 20% animal fat), 13% protein, and 47% carbohydrate (24 g fats, 24 g proteins, and 41 g carbohydrates per 100 g) was used for eight weeks (1). It should be noted that this study was performed according to the guidelines for the use and care of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a one-week adaptation to the laboratory environment, 24 rats were fed with standard HFD. To induce obesity, a fatty diet containing 45% of total energy from fat (20% soybean oil and 20% animal fat), 13% protein, and 47% carbohydrate (24 g fats, 24 g proteins, and 41 g carbohydrates per 100 g) was used for eight weeks (1). It should be noted that this study was performed according to the guidelines for the use and care of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, obesity is recognized as a major problem for global health and a multi-factorial physical disorder that results from high-calorie intake and low physical activity. Studies have shown that obesity is closely related to the development of diseases such as cardiovascular disease, cognitive impairment, cancer, motor disorders, and muscle mass loss (1). Metabolic syndrome is a collection of metabolic disorders such as high blood pressure, obesity, high blood triglycerides, and low levels of high-density lipoprotein (HDL), as well as insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a high fat diet (containing 45% of the total energy from fat (derived from animal fat) comprising 24 g of fat (saturated fatty acid), 24 g of protein, and 41 g of carbohydrate per 100 g) was used for obesity induction (1). The obese rats were then placed into obese control and training groups.…”
Section: Methodsmentioning
confidence: 99%
“…Low physical activity and consuming a high-calorie diet can induce obesity, which has become a major world health problem. It has been reported that some diseases such as motor disorders, cognitive disorders, cancer, metabolic syndrome, and cardiovascular disease are closely linked to obesity (1). Metabolic syndrome, which has a significant effect on cardiovascular disease-induced incidences of death, consists of some metabolic disorders, such as hypertension, obesity, lipid disorders, and increased insulin resistance (2).…”
Section: Introductionmentioning
confidence: 99%
“…As energy production is associated with hydrogen ion production, it increases hydroxyl radicals, thereby increasing pro-oxidant-antioxidant balance (PAB) as an enhancer of oxidative stress and impairing the function of proton vectors such as cytochrome c and ultimately damaging cellular DNA and apoptosis (5). Apoptosis is a programmed cell death involving several physiological and pathological events (6). Various studies have shown that exercise can increase antioxidant capacity and decrease oxidative stress (7) glutathione (GSH) and a set of functional enzymes that play a key role in cell defense against reactive free radicals and other ROSs (8).…”
Section: Introductionmentioning
confidence: 99%